Light-empowered contra-thermodynamic stereochemical editing - Wang, Peng-Zi; Xiao, Wen-Jing; Chen, Jia-Rong (Nature reviews. Chemistry, 2023)
Creating, conserving and modifying the stereochemistry of organic compounds has been the subject of significant research efforts in synthetic chemistry. Most synthetic routes are designed according to the stereoselectivity-determining step. Stereochemical editing is an alternative strategy, wherein the chiral-defining or geometry-defining steps are independent of the construction of the major scaffold or complexity. It enables late-stage alterations of stereochemistry and can generate isomers from a single compound. However, in many instances, stereochemical editing processes are contra-thermodynamic, meaning the transformation is unfavourable. To overcome this barrier, photocatalysis uses photogenerated radical species and introduces thermochemical biases. A range of synthetically valuable contra-thermodynamic stereochemical editing processes have been invented, including deracemization of chiral molecules, positional alkene isomerization and dynamic epimerization of sugars and diols. In this Review, we highlight the fundamental mechanisms of visible-light photocatalysis and the general reactivity modes of the photogenerated radical intermediates towards contra-thermodynamic stereochemical editing processes. Stereochemical editing is a strategy to access three-dimensional skeletons, where the stereochemistry-defining steps are decoupled from the major connectivity-forming reactions. This Review highlights recent advances in the area of light-driven contra-thermodynamic stereochemical editing.